An assessment of the antioxidant potential of coriander extracts in ghee when stored at high temperature and during deep fat frying. (27th December 2012) - Patel, Shriyesh; Shende, Sneha; Arora, Sumit; Singh, Ashish K
<x xml:space="preserve">Abstract</x> A coriander extract was evaluated for its potential to increase oxidative stability of ghee. Antioxidant activity using β‐carotene–linoleic acid model system and radical scavenging activity by 2‐diphenyl‐1‐picrylhydrazyl hydrate free (DPPH) was higher in steam distilled extract compared to its oleoresin counterpart. Steam distilled extract and oleoresin were significantly effective in retarding the deterioration of ghee relative to control, as observed in peroxide value, conjugated dienes, thiobarbituric acid (TBA) value and oxidative stability index at the end of 21 days of storage. However, these were less effective than butylated hydroxyanisole (BHA). During deep fat frying, steam distilled extracts showed higher antioxidant activity compared to oleoresin and BHA.